2017
DOI: 10.1364/boe.8.002287
|View full text |Cite
|
Sign up to set email alerts
|

Handheld optical coherence tomography angiography

Abstract: Abstract:We developed a handheld optical coherence tomography angiography (OCTA) system using a 100-kHz swept-source laser. The handheld probe weighs 0.4 kg and measures 20.6 × 12.8 × 4.6 cm 3 . The system has dedicated features for handheld operation. The probe is equipped with a mini iris camera for easy alignment. Real-time display of the en face OCT and cross-sectional OCT images in the system allows accurately locating the imaging target. Fast automatic focusing was achieved by an electrically tunable len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 39 publications
0
31
0
1
Order By: Relevance
“…In this context, a OCTA device has been introduced, which enables imaging in recumbent patients (Flex-Modul for SPECTRALIS ® , Heidelberg Engineering GmbH, Heidelberg, Germany) 25 . In addition, hand-held OCTA devices have been presented 40,41 .…”
mentioning
confidence: 99%
“…In this context, a OCTA device has been introduced, which enables imaging in recumbent patients (Flex-Modul for SPECTRALIS ® , Heidelberg Engineering GmbH, Heidelberg, Germany) 25 . In addition, hand-held OCTA devices have been presented 40,41 .…”
mentioning
confidence: 99%
“…In the last few years angio-OCT technology has gained popularity in the pediatric population and publications associated with amblyopia (16), myopic choroidal neovascular membrane (17) and others could be seen. In 2017 Yang et al developed a prototype of a handheld probe for angio-OCT with good quality of the exported images (18).…”
Section: Stationary Oct Technologymentioning
confidence: 99%
“…В последните няколко години, с навлизането на ангио-ОСТ технологията в клиничната практика, се появиха публикации при деца, асоциирани със състояния като амблиопия (16), миопична хориоидална неоваскуларна мембрана (17) и др. През 2017 г. Yang и съавтори разработват прототип на портативна сонда за ангио-ОСТ апарат с добро качество на получените образи (18).…”
Section: Partially Portable Hand-held Ct Technologyunclassified
“…There are a few research groups who have attempted the development of highperformance hand-held OCT/OCTA probe using high-speed (over 100kHz) swept-source laser for ROP screening. Yang and Campbell et al reported their light weight, 100 kHz Aline-rate handheld probe for OCTA applications and demonstrated high-quality OCTA images in awake adults and anesthetized infants [21,28]. Christian et al reported their 200 kHz A-line-rate handheld OCTA probe designed on an innovative '5F' (focus) optical system, demonstrating OCTA image of foveal area and optical nerve head [29].…”
Section: Introductionmentioning
confidence: 99%